THE USE OF SWELL IN TEACHING WRITING NARRATIVE TEXTS TO EIGHTH GRADERS - Nur Ainani Fitria (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
SWELL (Social-Interactive Writing for English Language Learners) is one of several techniques that can be used to improve the students‟ writing ability. It is known that many EFL (English For-eign Language) learners have problems in composing the essay. Therefore, the study of how SWELL can enhance the students‟ skill in writing narrative texts is important to be conducted. Moreover, none of researchers tries to reveal the use of SWELL in the teaching and learning of English as a foreign language. The purposes of this study are to describe how the teacher ap-plies SWELL in teaching writing narrative texts to eighth graders and the effects of using SWELL on the students‟ narrative writings. Focused on the enhancement of students‟ skill in writing narrative texts, this classroom action research was conducted at MTsN Model Treng-galek, East Java. To collect the data, observation checklist and students‟ tests were employed. The research showed that in applying SWELL in writing narrative texts, teacher did three ac-tivities, including opening activities, main activities, and closing activities. Meanwhile, based on the overall mean scores of the students‟ writings that improved from preliminary study to cycle II; 69.2, 76.41, and 76.47 and significant improvement on the students‟ class mastery of final drafts from preliminary study to cycle II; 35.3%, 76.5%, and 94.12%, there is a significant improvement on the students‟ writing ability that includes content, organization, vocabulary, language use, and mechanics by using this technique. To conclude, SWELL was successfully applied to improve the eighth graders‟ writing narrative texts. Key Words: SWELL, writing, and narrative text.